2012
DOI: 10.1016/j.celrep.2012.09.014
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Functional Screen Uncovers miR-150-Mediated Regulation of Hematopoietic Injury Response

Abstract: Summary Hematopoietic stem and progenitor cells are often undesired targets of chemotherapies, leading to hematopoietic suppression requiring careful clinical management. Whether microRNAs control hematopoietic-injury response is largely unknown. We report a novel in vivo gain-of-function screen and identification of miR-150 as an inhibitor of hematopoietic recovery upon 5-fluorouracil-induced injury. Utilizing a bone marrow transplant model with a barcoded microRNA-library, we screened for barcode abundance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 36 publications
(54 reference statements)
0
42
0
Order By: Relevance
“…miR-150-5p is evolutionarily conserved, and previous studies have shown it as a key regulator of the transcription factor c-Myb, a regulator of hematopoiesis in multiple lineages [36,37]. An in vivo gain of function screen has identified miR-150-5p as an inhibitor of hematopoietic recovery upon marrow injury induced by the chemotherapeutic agent 5-flurouracil [38], where depletion of miR-150-5p resulted in enhanced hematopoietic recovery [38]. Also, studies using miR-150 knockout mice shows its effect on inhibition of inflammation and apoptotic response after myocardial infarction induced acute kidney injury [39].…”
Section: Discussionmentioning
confidence: 99%
“…miR-150-5p is evolutionarily conserved, and previous studies have shown it as a key regulator of the transcription factor c-Myb, a regulator of hematopoiesis in multiple lineages [36,37]. An in vivo gain of function screen has identified miR-150-5p as an inhibitor of hematopoietic recovery upon marrow injury induced by the chemotherapeutic agent 5-flurouracil [38], where depletion of miR-150-5p resulted in enhanced hematopoietic recovery [38]. Also, studies using miR-150 knockout mice shows its effect on inhibition of inflammation and apoptotic response after myocardial infarction induced acute kidney injury [39].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, management of hematopoietic injury is a major clinical question in both chemo and radiation based cancer therapies. Recent studies show that miRNA-150 control hematopoiesis [29], [30], [31] and their dose and time dependent changes should provide readouts for the conditioning as well as hematopoietic injury response [31]. Recent genetic studies have shown that overexpression of miRNA-150 results in a slow recovery rate after 5-fluorouracil induced injury in a mouse model for bone marrow transplant [30].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of hematopoietic phenotypes were performed as previously described (Guo et al, 2012; Adams et al, 2012; Guo et al, 2010). Myeloid bias index was used to quantify biased differentiation into myeloid lineages, which was calculated by (%GFP+Mac1+)/(%GFP+Mac1−)/((%GFP−Mac1+)/(%GFP−Mac1−)).To examine monocytic differentiation bias, Mac1+ cells from GFP+ fraction (transduced) were gated before examining Ly6C and Ly6G distribution.…”
Section: Methodsmentioning
confidence: 99%